Rural And Urban Land And Building Tax Calculation Application (PBB-P2): Case Study Of Cangkuang Wetan Village - Noerrohmah, Syifa; Amijaya, Hasanah Tisna; Riswaya, Asep Ririh; Retnowaty, Agung Tri (Acman: Accounting and Management Journal, 2024)
The PBB-P2 application, which focuses on the case study of Cangkuang Wetan Village, is specifically created to streamline and enhance the inputting and managing of rural and urban land and building taxes. The data-gathering methods employed, including thorough observation, comprehensive interviews, and extensive literature review, ensure the accuracy and reliability of the system. The system design was created with descriptive techniques and the object-oriented analysis and design (OOAD) development methodology, employing, which involves a process of analysis, system design, and object-oriented implementation outlinas ed by the Unified Modeling Language (UML). This design aims to provide benefits to Cangkuang Wetan Village by automating the tax computation process, managing citizen data, and generating time-saving reports.